A fundamental approach to transformer thermal modeling. II. Field verification. - Swift, G.
For pt.I see ibid., vol.16, no.2, p.171-5 (2001). This paper has two main objectives. One is to show that the top oil rise thermal model proposed in part I is valid, for a large power transformer in service. The second is to show that there is a convenient way of estimating the parameters without removing the transformer from service. A Manitoba Hydro 250 MVA OFAF transformer was chosen and instrumented with data-gathering equipment. Two twenty-four hour test runs were performed, one in February of 1999 and the other in July of 1999. The most basic parameter to be determined was the rated top oil rise but also found were the top oil line constant and the nonlinearity exponent, commonly given the symbol n. The results are very positive
Keywords: 24 h; 250 MVA; Manitoba Hydro OFAF transformer; Data-gathering equipment; Nonlinearity exponent; Parameters estimation; Power transformer; Power transformer protection; Rated top oil rise determination; Thermal factors; Top oil line constant; Top oil rise thermal model; Transformer thermal modeling